2011
DOI: 10.1002/jor.21484
|View full text |Cite
|
Sign up to set email alerts
|

The relationships among spatiotemporal collagen gene expression, histology, and biomechanics following full‐length injury in the murine patellar tendon

Abstract: Tendon injuries are major orthopaedic problems that worsen as the population ages. Type-I (Col1) and type-II (Col2) collagens play important roles in tendon midsubstance and tendon-to-bone insertion healing, respectively. Using double transgenic mice, this study aims to spatiotemporally monitor Col1 and Col2 gene expression, histology and biomechanics up to 8 weeks following a full-length patellar tendon injury. Gene expression and histology were analyzed weekly for up to 5 weeks while mechanical properties we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
53
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 44 publications
(58 citation statements)
references
References 17 publications
(27 reference statements)
5
53
0
Order By: Relevance
“…Three weeks after injury, Egr1 and Col1a1 were still overexpressed at the sites of tendon injury compared with basal expression in the control tendons (Figure 4D). The massive upregulation of tendon gene expression after Achilles tendon injury is consistent with other studies in murine tendon injury models (26,27). We next examined the requirement for Egr1 in the gene response during the tendon healing process.…”
Section: Egr1 Deficiency Affects Tendon Gene Expression During Achillsupporting
confidence: 84%
“…Three weeks after injury, Egr1 and Col1a1 were still overexpressed at the sites of tendon injury compared with basal expression in the control tendons (Figure 4D). The massive upregulation of tendon gene expression after Achilles tendon injury is consistent with other studies in murine tendon injury models (26,27). We next examined the requirement for Egr1 in the gene response during the tendon healing process.…”
Section: Egr1 Deficiency Affects Tendon Gene Expression During Achillsupporting
confidence: 84%
“…In a study that used fluorescently tagged collagen I and collagen II genes to investigate murine patellar tendons injured with a central, full-thickness defect, elevated levels of collagen I expression were measured near the insertion sites at 1 week postinjury, whereas elevated expression in the midsubstance was delayed, peaking 1 week later. Collagen II expression, however, was not observed during the healing response (62). The accessibility of murine primers and antibodies for biological assays is yet another advantage of this injury model, as evinced by a recent study measuring increased expression of the tendon marker scleraxis, previously known only for its role in tendon development, 4 weeks after patellar tendon injury in mice (63).…”
Section: Injury and Healing In Mouse Tendonsmentioning
confidence: 88%
“…On the basis of studies on horses, rabbits, and rats 39,40,[51][52][53][54][55][56] , given that obtaining human biopsy samples can be difficult, it has been shown that following tendon injury, the natural healing process forms scar tissue via a three-stage process: inflammation, matrix production, and remodeling and maturation 39,40 . The inflammatory stage initiates the response to injury, typically throughout the first week 39 .…”
Section: Natural Healingmentioning
confidence: 99%
“…Cell density and vascularity decrease as the tissue further repairs 40 . Studies have shown that natural healing leads to tendon biomechanical properties that fail to match normal levels at up to eight weeks, twenty-six weeks, and twelve months following injury in a murine and rabbit central patellar tendon model, and sheep Achilles tendon model, respectively [51][52][53] . Investigators have suggested the poor mechanical properties result from predominantly small fibrils in the resulting repair tissue, compared with the normal distribution of both large and small fibrils observed in normal adult human tendon 54,55 , but conflicting results exist.…”
Section: Natural Healingmentioning
confidence: 99%